The future of life - Edward O. Wilson (London Abacus, 2003)
From one of the world's most influential scientists (and two-time Pulitzer Prize-winning author) comes his most timely and important book yet: an impassioned call for quick and decisive action to save Earth's biological heritage, and a plan to achieve that rescue.
Includes Index
Keywords: Endangered species; Nature conservation; Environmental degradation